1996
DOI: 10.1007/s004649910096
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery in the rat Beneficial effect on body weight and tumor take

Abstract: Laparoscopic surgery is associated with less postoperative weight loss and less tumor take compared to open surgery. CO2 insufflation appears to increase tumor take.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 0 publications
4
54
0
Order By: Relevance
“…Jacobi et al 32 showed that the simple act of creating a CO 2 pneumoperitoneum caused increased tumor growth within the peritoneal cavity. Work by Bouvy et al 33,34 using both cell suspension and solid tumor models achieved similar results. In contrast, the results of Hubens and Eyskens 35 showed no difference in the rate intraperitoneal tumor growth between anesthetic controls and CO 2 insufflation.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Jacobi et al 32 showed that the simple act of creating a CO 2 pneumoperitoneum caused increased tumor growth within the peritoneal cavity. Work by Bouvy et al 33,34 using both cell suspension and solid tumor models achieved similar results. In contrast, the results of Hubens and Eyskens 35 showed no difference in the rate intraperitoneal tumor growth between anesthetic controls and CO 2 insufflation.…”
Section: Discussionmentioning
confidence: 61%
“…38 However, studies generally demonstrate that this effect is less with laparoscopy. [32][33][34][35]39 These studies have examined the effects of laparoscopy on tumor growth at a site remote from the peritoneal cavity, such as the animal's flank, and may help to explain some of the differences between their findings and our study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4,5 Previously described clinical and experimental studies showed that surgical trauma promotes intra-abdominal tumor recurrence. [6][7][8] In an animal experimental study Raa et al 9 showed that this effect is mainly due to enhanced adhesion of tumor cells rather than enhanced growth of already adhered tumor cell clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Bouvy et al [2], who have provided some helpful insights into the behavior of malignant tumor cells during laparoscopic surgery. As with work previously reported by Allendorf et al [1], they have demonstrated that laparoscopic procedures may be associated with reduced growth of tumor cells in a smallanimal model.…”
mentioning
confidence: 99%